Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1991
DOI: 10.1165/ajrcmb/4.1.72
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of Humans to Ambient Levels of Ozone for 6.6 Hours Causes Cellular and Biochemical Changes in the Lung

Abstract: An acute (2 h) exposure of humans to 0.4 ppm ozone initiates biochemical changes in the lung that result in the production of components mediating inflammation and acute lung damage as well as components having the potential to lead to long-term effects such as fibrosis. However, many people are exposed to lower levels of ozone than this, but for periods of several hours. Therefore, it is important to determine if a prolonged exposure to low levels of ozone is also capable of causing cellular and biochemical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
242
2
7

Year Published

1993
1993
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 448 publications
(265 citation statements)
references
References 44 publications
11
242
2
7
Order By: Relevance
“…Epidemiological studies have found associations between low ozone levels and: 1) decline in pulmonary functions (Galizia and Kinney, 1999;Folinbee et al, 1988;Kinney et al, 1996;Devlin et al, 1991); 2) increase in hospital admissions for asthma, especially among children (Stern et al, 1994;Galizia and Kinney, 1999); and 3) congestive heart failure among the elderly (Burnett et al, 1997b). Positive associations between short-term 1-hour max ozone levels and mortality, adjusted for the potential confounding effects of other pollutants and weather, have been found in Los Angeles and New York (Kinney and Ozkaynak, 1991;Kinney et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological studies have found associations between low ozone levels and: 1) decline in pulmonary functions (Galizia and Kinney, 1999;Folinbee et al, 1988;Kinney et al, 1996;Devlin et al, 1991); 2) increase in hospital admissions for asthma, especially among children (Stern et al, 1994;Galizia and Kinney, 1999); and 3) congestive heart failure among the elderly (Burnett et al, 1997b). Positive associations between short-term 1-hour max ozone levels and mortality, adjusted for the potential confounding effects of other pollutants and weather, have been found in Los Angeles and New York (Kinney and Ozkaynak, 1991;Kinney et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The health effects associated with short-term exposure to ambient ozone are well documented in air pollution studies (Galizia and Kinney, 1999;Devlin et al, 1991;Folinbee et al, 1988;Kinney et al, 1996;Stern et al, 1994;Levy et al, 2001;Kelsall et al, 1997;Moolgavkar, 2000;Thurston and Ito, 2001;Glodberg et al, 2001). Exposure to ozone levels less than 100ppb can irritate the respiratory tract, particularly for sensitive populations, concentrations above 300ppb can cause nose and throat irritation, and levels above 1000ppb (typical levels in very smoggy air) can cause breathing problems and headaches.…”
Section: Introductionmentioning
confidence: 99%
“…Some investigators have found that ozone was significantly associated with cardiac hospital admissions (Burnett et al, 1997a;Ponka and Virtanen, 1996 ), whereas several others have found no association or a borderline significant association ( Burnett et al, , 1997b( Burnett et al, , 1999Morris et al, 1995;Poloniecki et al, 1997;Schwartz, 1997;Schwartz and Morris, 1995 ). Although the respiratory pathophysiology of ozone is relatively well understood (Crapo et al, 1992;Devlin et al, 1991;Vincent et al, 1997 ) , effects on the cardiovascular system are not. Cardiovascular effects may occur by way of a nonspecific insult, perhaps mediated through the respiratory system ( Bouthillier et al, 1998) .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the link between current measures of acute symptomatic and/or functional responses to ozone (6,7) and the occurrence of chronic effects has not been established in humans, nor has it been established that the mechanisms that underlie acute effects [e.g., airways hyperreactivity (8), reflex neural alterations of measured vital capacity (9), inflammatory changes (10)] are the same as those that underlie chronic effects (e.g., loss of lung elastic recoil, deposition of excess collagen).…”
Section: Introductionmentioning
confidence: 99%